A Conceptual Framework of Digital Marketing, Brand Image, and Product Quality Towards Repurchase Intention of Frozen Food Products Through Purchase Decision of Kingko Food Jakarta. - Adipradana, Yoga; Harwani, Yuli (Dinasti Publisher, 2023)
Kingko Food, a small and medium-sized enterprise in the frozen food industry, has encountered a significant decline in sales over the past three years. This research aims to conceptualize the influence of digital marketing, brand image, and product quality on the intention to repurchase frozen food products. A particular focus is placed on the role of purchase decisions as an intermediary factor. The study adopts a quantitative methodology and a causal design approach. It targets consumers who have previously purchased from Kingko Food, exploring how their perceptions and experiences, shaped by digital marketing efforts, brand image, and the quality of the products, contribute to their decision to repurchase. The research seeks to map out the direct and indirect impacts of the three key variables – digital marketing, brand image, and product quality – on customer repurchase intention. In particular, it examines how these factors influence the purchase decision process, hypothesized to affect the likelihood of customers repurchasing the product. By delving into these relationships, the study aims to provide deeper insights into the determinants of customer loyalty and repeated purchase behavior in the context of the frozen food market. These insights are expected to be valuable for strategic marketing and product management decision-making, especially for SMEs like Kingko Food, facing market challenges.